ACADEMIC LEADERSHIP IN DIGITAL AGE OF EXPANDING EDUCATIONAL OPPORTUNITY SCHOOL ADMINISTRATOR IN UTTARADIT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Sudte, Maneerat; Kamolvoradej, Yokkaew; Sanghirun, Manee (Journal of MCU Nakhondhat, 2020)
The objective of this research paper is to study the current conditions. And to study the ways of academic leadership in the digital age of school administrators in educational opportunity expansion schools. Of Uttaradit Primary Educational Service Area Office 2. Population used in the research were 1) 355 administrators and teachers. 2) The Director of the Deputy Director of Educational Supervisors from the Office of Uttaradit Primary Educational Service Area 2, the administrators and teachers who have received the award for teaching. Head of Academic and Uttaradit Rajabhat University lecturers, amount 12 people, using the specific selection method. The research instruments were questionnaires and in-depth interviews. The statistics used for data analysis were percentage, mean and standard deviation. The results of the research revealed that 1) Academic leadership in the digital age. In general, it is at a high level. 2) The way of academic leadership in the digital age. Academic planning Administrators should have a survey and inquire about the need for technology to be used in the teaching and learning of teachers, indicating that teachers are aware of the importance of using technology. Encourage teachers to have self-development always Management The administrators created the school database system by using technology to help store the data to be correct. Modern and has a variety of access channels. Promoting academic atmosphere Administrators should have a SWOT then to define the vision and strategy plan according to the school environment. Build cooperation between schools and communities. Providing an atmosphere of learning that is conducive to support the technology. Regarding to supervision, administrators should observe various types of teacher teaching. There was a meeting explaining the strengths of teaching using technology and innovation in teaching and learning.